Islamic desk reference - Donzel, E. J. van (E.J. Brill, 1994)
The growing demand for concise and factual information about the history and culture of Islam has now been met with the "Islamic Desk Reference," This handy one-volume work contains a condensation of the subject-matter of "The Encyclopaedia of Islam," the most prestigious and valuable reference work for Islamic studies published this century. In a brief, orderly and intelligible form the "Islamic Desk Reference" provides thus a unique and valuable quick reference tool for those interested in the religion, the believers and the countries of the Islamic world. All entries in the "Islamic Desk Reference" are given in English. Thus, names of Arabic origin which in the West were corrupted to another spelling, e.g. Ibn Sina to Avicenna, al-Kuhl to alcohol, are found under the latter term. The "Islamic Desk Reference" contains maps, diagrams and genealogical tables for easy reference, and illustrations